Strategi Manajemen Konflik dalam Perspektif Al-Qur’an dan Hadis - Nurhamidin, Candra Puspita; Yahiji, Kasim (Jurnal Pendidikan Islam, 2024)
Conflict doesn't only occur in a society or organizational group; it can also arise within each individual. Dealing with conflict requires accurate handling through conflict management. By examining and delving into conflict management strategies, it can help minimize conflicts in society, organizations, and educational institutions. This study aims to examine conflict management strategies from the perspective of the Qur'an and Hadith. This study employs a qualitative approach with literature study/data collection techniques originating from books, articles, and journals that discuss conflict management strategies from the perspective of the Qur'an and Hadith. The study's findings indicate that conflict management is a strategy for groups, organizations, and individuals to anticipate disputes and disagreements among individuals. Conflicts can stem from human and organizational factors. Approaches that can be implemented in conflict include using compromising styles, avoiding styles, dominating styles, following the will, and collaborative styles. Conflict management strategies that can be implemented from the perspective of the Qur'an and Hadith include negotiation, verification, consultation, arbitration, and reconciliation.